Polyporus Shoreae Root Rot on Sal - Bakshi, B. K.; Boyce, J. S. (Indian Forester, 1959)
A root rot disease of sal caused by Polyprus shoreae results in top dying and death of trees in North Bengal and Assam. In many cases, the dying trees become windthrown due to roots becoming decayed and loosing footholds in the soil. The disease is correlated with high rainfall. The fungus infects through healthy uninjured roots, causing decay in the bark and sapwood. Heartwood is unaffected. The decay does not normally progress into the stem. Till the disease is worked out, the suggested control measures include removal of dying and dead trees and practising controlled burning to reduce soil moisture.